Genome-Wide Identification of the PAP Gene Family in Potatoes and Its Expression Response to Phosphorus-Solubilizing Bacteria, Freezing Stresses, and Phytohormonal Regulation - Li, Chengchen; Liu, Jitao; Liao, Yongshan; Luo, Huanming; Wang, Li; Shan, Jianwei; Suo, Haicui; An, Kang; Yang, Kun; Li, Xiaobo (Agronomy (Basel), 2024)
Purple acid phosphatases (PAPs) are multifunctional proteins implicated in various aspects of plant biology, including flowering, seed development, senescence, carbon metabolism, and the response to biotic and abiotic stresses. Although PAPs have been reported in potatoes, the gene features and expression under phosphorus-solubilizing bacteria and freezing stresses remain unclear. In the present study, we identified 29 StPAPs with molecular weights ranging from 27.96 to 85.40 kDa, which were classified into three distinct groups based on a phylogenetic analysis. Integrating gene chromosomal localization, gene duplication events, intergenic collinearity, and gene selection pressure analysis, we found that the expansion of the potato PAP gene family was primarily driven by genome-wide duplication events, with the majority of the PAP genes undergoing purifying selection. Promoter cis-acting element analysis and RNA-Seq data revealed that a total of 89 cis-acting elements were associated with plant hormones, and the seven StPAP genes for low phosphorous response were associated with responses to abscisic acid, gibberellin, and abiotic stresses. Tissue expression pattern analyses indicated that the expression of StPAP genes were regulated in response to varying phosphorus levels. A co-expression network analysis identified eight StPAP genes involved in symbiosis with phosphorus-solubilizing bacteria, and seven StPAP genes exhibited significantly higher expression in response to freezing stress and abiotic stresses (drought, heat, darkness, and N/K/Ca/Fe/Mg/Zn deficiencies). In conclusion, the StPAP may synergistically modulate phytohormone levels in response to stress by regulating plant phosphorus homeostasis; StPAP12 and abscisic acid are key phosphorus-regulated genes and phytohormones in response to freezing stress. This study represents the first report to demonstrating the responsiveness of StPAPs to phytohormones, revealing a potential new function for these genes in plant stress responses and nutrient management. These findings provide novel insights into the multifaceted roles of PAPs in plant adaptation and stress tolerance.